THE STUDY OF ADMINISTRATION EXTRACT KEBAR GRASS ON NUMBER LEYDIG CELLS AND SERTOLI CELLS IN RAT (Rattus norvegicus) THAT EXPOSED WITH CIGARETTE SMOKE - Unitly, Adrien Jems Akiles (Universitas Pattimura, 2019)
This research aimed to study on the microscopic changes of number leydig cells and sertoli cells. A factorial CRD with periode of treatment and sample collection was applied in this study. An exposure of cigarette smoke was carried out at 10 cigarettes/rat/day for 2.5 hours in a smoking chamber. Extract kebar’s grass given was 0.0945 mg/g body weight/day. Twenty seven (27) of male rats were divided into four groups. N group was untreated animals, 20h group is group that was expose to cigarette smoke for 20 days then given administration extract kebar’s grass for 20 days and stopping treatment for 20 days and 60h group is group that was expose to cigarette smoke for 60 days then given administration extract kebar’s grass 60 days and stopping treatment for 60 days. Data collection was carried out at twice that after cigarette smoke exposure (T0), second after administration extract kebar’s grass (T1) and third after stopping treatment (T2). The parameters measured were the number of leydig cells and sertoli cells. That increasing number leydig cells and sertoli cells of rat exposed to cigarette smoke after gived seaweed extract kebar’s grass for 20 days and